1989
DOI: 10.1007/bf00558514
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of suckable tablets of oral N-acetylcysteine in man

Abstract: The pharmacokinetics and bioavailability of suckable tablets and granules of N-acetylcysteine (NAC) have been compared after oral administration of 400 mg doses to 10 healthy volunteers. The oral bioavailability of the NAC tablets was 103%. In a multiple dosing study of the same tablets in the same subjects, a high maintenance plasma level of NAC was revealed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

1991
1991
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 7 publications
0
3
1
Order By: Relevance
“…Plasma concentrations of total cysteine and GSH were elevated after NAC ingestion. Previous pharmacokinetic studies suggest NAC plasma levels peak 45 min after oral administration 2, 5. This was not the case in our study.…”
Section: Discussioncontrasting
confidence: 61%
“…Plasma concentrations of total cysteine and GSH were elevated after NAC ingestion. Previous pharmacokinetic studies suggest NAC plasma levels peak 45 min after oral administration 2, 5. This was not the case in our study.…”
Section: Discussioncontrasting
confidence: 61%
“…Although N-acetyl-L-cysteine does not occur naturally, it is used as a drug ("Mucomyst") to reduce lung congestion (Friedman, 1973). The compound is an excellent nutritional source of cysteine for humans and animals (De Bernardi di Valserra et al, 1989;Friedman and Gumbmann, 1984), and acts as an antimutagen and anticarcinogen (De Flora et al, 1989;Friedman et al, 1982a;Stevens et al, 1995). Efforts are continuing to develop sulfite substitutes for browning prevention in potatoes and other foods.…”
Section: Dietary Significancementioning
confidence: 99%
“…and Gumbmann, 1988) relpotency (%) Our studies revealed that IV-acetyl-L-cysteine is an excellent source of L-cysteine in vivo; i.e., the ability of the IV-acetyl derivative to substitute for L-methionine for mice turned out to be even better than that of L-cysteine itself Gumbmann, 1984, 1988). N-Acetyl-Lcysteine is also well-utilized by humans (De Bernardi di Valserra et al, 1989).…”
Section: Biological Utilization and Safety Of Sulfur Amino Acidsmentioning
confidence: 99%